Coverage of Tuberculosis Reporting, Lopburi Province, Fiscal Year 2016 - Thaemcharoen, Thanakarn; Swaddiwudhipong, Witaya; Silaporn, Patummal; Bamrungpong, Noppapong (Journal of Medical and Public Health Region 4, 2020)
The objectives of the study were to determine coverage (sensitivity) of the tuberculosis reporting system (Tuberculosis Case Management, TBCM) and provide recommendations for improvement of the system in Lopburi Province, fiscal year 2017. The study was carried out in one general and one community hospitals with the most reported cases of TB in fiscal year 2017. TB data from the hospital data sources were compared with those from the TBCM. Hospital data sources included medical records of patients with ICD10 coding of TB, those from TB clinic and AIDS clinic, those receiving rifampicin treatment, HIV patients with TB screening, and those with stupum positive for TB by laboratory examination. In the study general hospital, 416 TB cases were detected from the hospital data sources and 346 cases were from the TBCM, giving the coverage of 83.2%. In the study community hospital, 125 TB cases were detected from the hospital data sources and 115 cases were from the TBCM, giving the coverage of 92.0%. Of the 70 TB cases with no TBCM reporting in the general hospital, 32 (45.7%) were not registered, 28 (40.0%) died before registration and 10 (14.3%) were referred out. Of the 10 TB cases with no TBCM reporting in the community hospital, 7(70.0%) were referred out and 3 (30.0%) died before registration. The median duration between registration and TB diagnosis was 15 days with a range of <1-246 days for the general hospital and 1 day with a range of <1-70 days for the community hospital. It is essential to increase coverage of TB reporting system, not only for management of TB patients but also for planning TB prevention and control programs.